The Effects of Bacille Calmette-Guerin Immunization and Contact History on the Risk of Leprosy: Meta Analysis of Case Control Study - Priscilla Jessica Pihahey; Bhisma Murti; Yulia Lanti Retno Dewi (Masters Program in Public Health, 2020)
Background: Leprosy or Hansen's is an infec